Mobilisasi Sumberdaya dalam Program Percepatan dan Penurunan Stunting di Wonosobo - Midhol, Ahmad Baihaqi (Jurnal Manajemen dan Ilmu Administrasi, 2025)
Wonosobo Regency is one of the areas with high stunting rates in Indonesia, with a prevalence reaching 20.22% in 2021. Based on the health service's work plan for accelerating and reducing stunting, it is carried out through several activities, including: Provision of Iron Tablets, Pregnancy Check-ups and Screening, Provision of Additional Food for Pregnant Women, Toddlers and Toddlers, Strengthening Exclusive Breastfeeding. However, although various efforts to accelerate stunting reduction have been carried out by the Wonosobo regional government, the success of this program is highly dependent on effective resource mobilization. This study will analyze how resource mobilization is carried out in the stunting reduction acceleration program in Wonosobo. The results of this study indicate that there are three main categories that are the focus of mobilization. First, government resource mobilization. Second, non-government resource mobilization. Third, academic participation.